Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian di Blok F Pasar Tanah Abang, Jakarta - Khairunnisa, Khairunnisa; Syahyuni, Dedy; Herliana, Khotimah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Competition between traders offering similar products with varying prices and quality, thus influencing consumer considerations in making purchases. In addition, most buyers are traders who are looking for products with affordable prices but still have the appropriate quality for resale. The purpose of this study is to determine how much influence price and product quality, both partially and simultaneously, have on purchasing decisions in Block F Tanah Abang Market, Jakarta. The research method used is a quantitative method based on statistical data with survey techniques through distributing questionnaires using Google Forms and data processed using SPSS version 26 with a sample of 96 respondents. The results of the study indicate that partially price influences purchasing decisions, while product quality does not influence purchasing decisions. However, simultaneously price and product quality have a significant effect on purchasing decisions in Block F Tanah Abang Market, Jakarta, this is evidenced by the calculated F value of 4.438 and a significance value of 0.001. The coefficient of determination (R2) value of 0.087 shows that 8.7% of purchasing decisions can be explained by the variables of price and product quality, while the remaining 91.3% is influenced by other factors not included in this study.